Representaciones acerca de la lectura de los docentes del nivel terciario del Instituto Nicolás Avellaneda - García, Luis María; Vides, María Eugenia; Apaza, Francisco Edmundo; Carrizo, Estela del Valle (Anuario Digital de Investigación Educativa, 2019)
Ninguno